Treasures from UCL - Furlong, Gillian (UCL Press, 2015)
UCL has one of the foremost university Special Collections in the UK. It is a treasure trove of national and international importance, comprising over a million items dating from the 4th century AD to the present day. Treasures from UCL draws together detailed descriptions and images of 70 of the most prized items. Between the magnificent illuminated Latin Bible of the 13th century and the personal items of one of the 20th century's greatest writers, George Orwell, the many highlights of this remarkable collection will delight and intrigue anyone who picks up this book.